Numerical Modelling of Two Dimensional Dam Break with Heavy Flow using Ansys Software - Nik Muhammad Azmi, Nik Ahmad Irfan; Amir, Muhammad Afiq Hakimi; Sukor, Anis Suzana; Idris, Nur'ain (Multidisciplinary Applied Research and Innovation, 2023)
In tracing the current era of modernization, simulation techniques have become an alternative option for measuring dam-break flow due to the rapidity of the development of computer technology. The main purpose of this project is to make a model and simulate the dam breaks according to the Lobovský(2014) experiment. To model and simulate the 2D heavy flow of dam break particle model using Ansys Software. To validate the results, obtained from simulation with the experimental by Lobovský(2014). The physical experimental carried out by Lobovský(2014), included the length of the tank in this simulation of 1610mm. The reservoir part region is 600mm and the dry part is 1010mm. 5 sensors were placed in several places on the wall of the tank to take the results when running the simulation. To carry out this project, Ansys software was used to make the particle dam break model and then the simulation. The fourth sentence presents key findings and trends that can be observed from the data. The fifth sentence summarizes the discussion regarding those findings and some suggestions for future work. The major goal of this study is to estimate how much harm will be caused when the dam breaks. The use of simulation is a great way to predict how breaking the dam would affect the surrounding area. It can save costs and be produced on both a small and large scale by employing simulation. Additionally, since they can be performed anywhere using a laptop and the Ansys software (fluent), simulations don't waste time. This simulation using the research from the article to validate the dam break's history and the water deformation.